Pengaruh suplementasi tepung limbah udang pada pengolahan pakan ikan dengan konsentrasi berbeda - Gusliany Gusliany; Tania Serezova Augusta (Fakultas Peternakan Universitas Kristen Palangka Raya, 2018)
This research is aimed to obtain the amount of substituting shrimp waste flour for an optimum fish feed. This research was using Complete Random Design with 4 (four) treatments and 3 (three) replications. Treatment A, B, C, and D were giving shrimp waste flour 0%, 12.5%, 25.0%, and 37.5% of fish feed weight respectively. Data collection based on the result of chemical test, organic test and physical test on the fish food. The result of chemical test on fat content and water content approves that treatment D is the best application with 11.15% of fat content and 5.02% of water content. Organism test showed that treatment C (25%) was the best result of fish growth (12.5%) during 21 days of treatment.